An AMS method to determine analyte recovery from pharmacokinetic studies with concomitant extravascular and intravenous administration. (February 2011) - Lappin, Graham; Seymour, Mark; Young, Graeme; Higton, David; Hill, Howard M
The absolute bioavailability, clearance and volume of distribution of a drug can be investigated by administering a very low dose of the 14 C-drug intravenously along with a therapeutic nonlabeled dose by the extravascular route (typically orally). The total drug concentration is measured by an assay such as LC––MS and the 14 C-drug is measured by accelerator MS (AMS). In another article in this issue, a method validation is proposed where AMS was used as the analytical assay. Part of the validation is to assess the recovery of the analyte being measured as this has a direct impact on its quantification. In this article, a method of internal standardisation is described where the UV response of the nonlabeled analyte, spiked in excess into the matrix being analysed, is used for internal standardization. The method allows for the recovery of analyte to be measured in each individual sample being analysed. It is important to know the recovery of a 14 C-labeled analyte when determining its mass concentration from 14 C: 12 C isotopic ratio data using AMS. A method is reported in this article that utilizes the UV response of the nonlabeled drug for internal standardization, so that the recovery for each individual sample analyzed can be ascertained.